2006
DOI: 10.1128/mcb.01148-06
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedin U Receptor 2-Deficient Mice Display Differential Responses in Sensory Perception, Stress, and Feeding

Abstract: Neuromedin U (NMU) is a highly conserved neuropeptide with a variety of physiological functions mediated by two receptors, peripheral NMUR1 and central nervous system NMUR2. Here we report the generation and phenotypic characterization of mice deficient in the central nervous system receptor NMUR2. We show that behavioral effects, such as suppression of food intake, enhanced pain response, and excessive grooming induced by intracerebroventricular NMU administration were abolished in the NMUR2 knockout (KO) mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 50 publications
4
64
0
Order By: Relevance
“…In addition, it is also unclear why NMU KO mice develop obesity (Hanada et al 2004), whereas NMUR2 KO mice are lean and smaller than normal (Zeng et al 2006, Novak 2009, Peier et al 2009). Of course, as mentioned above, NMS may act on an undefined receptor other than NMU1R and NMU2R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is also unclear why NMU KO mice develop obesity (Hanada et al 2004), whereas NMUR2 KO mice are lean and smaller than normal (Zeng et al 2006, Novak 2009, Peier et al 2009). Of course, as mentioned above, NMS may act on an undefined receptor other than NMU1R and NMU2R.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence accumulated over the last decade has suggested that NMU and/or NMS are involved in the central regulation of feeding, energy homeostasis, stress, and circadian rhythms, probably through NMUR2 , Hanada et al 2001, Ivanov et al 2002, Nakahara et al 2004a,b, Ida et al 2005, Novak et al 2006, Zeng et al 2006, Novak 2009, Peier et al 2009). I.c.v.…”
Section: Introductionmentioning
confidence: 99%
“…GPR54 KO mice were produced by retroviral mutagenesis as described previously (Krasnow et al, 2004;Zeng et al, 2006). Briefly, an embryonic stem (ES) cell library was constructed by infecting 129/Sv ES cells with a retroviral vector that included a selection marker, termination codons in all reading frames, a splice adaptor, and a transcription terminator to ensure gene inactivation after insertion.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the NK1 receptor, the neuromedin U2 receptor (NMU2) plays a central role in nociception. NMU2 knockout mice display reduced sensitivity to pain induced by capsaicin and formalin [46] .…”
Section: Gpcrs and Inflammatory Painmentioning
confidence: 99%